Evaluation of buildings’ redevelopment alternatives with an emphasis on the multipartite sustainability - Zavadskas, Edmundas Kazimieras; Antuchevičiene, Jurgita (International Journal of Strategic Property Management, 2010)
The authors analyse the problem of derelict buildings’ redevelopment by means of multi criterion decision‐making techniques. The aim of the research is to rank derelict buildings’ redevelopment alternatives from the multiple sustainability approach. Moreover, handling of MCDM techniques is discussed. The MCDM techniques used are: technique for order preference by similarity to ideal solution (TOPSIS) and compromise ranking method (VIKOR). A Lithuanian case study is presented to illustrate similarities and differences of ranking results using these methods in particular situation. The comparisons of the results after multiple criteria analysis implementation are made in the paper and scientific recommendations for a sustainable redevelopment of derelict buildings in Lithuanian rural areas are suggested on a basis of calculations.First Published Online: 18 Oct 2010